The 60th anniversary of the discovery of DNA secondary structure - Brajušković, Goran N; Savić Pavićević, Dušanka; Romac, Stanka (Vojnosanitetski pregled, 2017)
Key words: DNA; molecular biology; genomics; history of medicine; nobel prize.